(3JMQjQ GdbhGYO GdefWbjI aj TQM GdTeSjIs - (3GdQGRj, GdbWH GdJMJGfj, eMeO Hf eMeO, J (B766 (3g`s
(3ChdgG (B:s
(3NaV ddCUMGH GdaVd LfGM GdCaVGd MJi LdH Edi NHGH QaYI HVGjY GdYdhe ef cd eQej SMjb s
(3BNQgG (B:s
(3hBNQg GdbSe GdQGHY eG jJQcH ef GdLedjI hGdefaUdjI QGHY GdCbSGe eG jJQcH ef GdLedjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7/38s
(3eYLe GdeDdajf (B3/642s
(3cTa GdXfhf (B2/ 1063s
(3TPQGJ GdPgH (B6/207s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdadSaI hGdefWbs